2008
DOI: 10.2174/1874082000802010016
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Depression in Phasic Motor Nerve Terminals and Influence of 5-HT on Vesicle Dynamics

Abstract: Synaptic depression that is induced by electrical stimulation of the glutamatergic neuromuscular junction (NMJ) of the crayfish can be offset by recruitment of vesicles from a presynaptic reserve pool. This recruitment occurs following treatment of the NMJ with serotonin (5-HT), which results in a delay in the onset of synaptic depression induced by high frequency stimulation. The results of this study demonstrate that the releasable vesicles are insufficiently replenished during high frequency stimulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
6
1
Order By: Relevance
“…Recently, studies have shown that with high frequency stimulation, vesicles can be endocytosed by a bulk process thus allowing a large number of vesicular fusion events to occur at the synapses but without distorting the synaptic area [50]. In high-output NMJs of the crayfish on the extensor muscle, we did not observe bulk endocytosis with prolonged stimulation in a recent study [51], so we would not expect to find bulk endocytosis during these relatively short pulse trains for the low-output NMJs used in this current study. Some variation in the probability of release over the pulse train could be induced due to glutamate-ergic autoreceptor presynaptic feedback [52].…”
Section: Discussioncontrasting
confidence: 52%
“…Recently, studies have shown that with high frequency stimulation, vesicles can be endocytosed by a bulk process thus allowing a large number of vesicular fusion events to occur at the synapses but without distorting the synaptic area [50]. In high-output NMJs of the crayfish on the extensor muscle, we did not observe bulk endocytosis with prolonged stimulation in a recent study [51], so we would not expect to find bulk endocytosis during these relatively short pulse trains for the low-output NMJs used in this current study. Some variation in the probability of release over the pulse train could be induced due to glutamate-ergic autoreceptor presynaptic feedback [52].…”
Section: Discussioncontrasting
confidence: 52%
“…The vesicles in the RP pool are recruited under particular circumstances such as high frequency stimulation or in the presence of neuromodulators like 5-HT for crayfish NMJs (Wang and Zucker, 1998;Quigley et al, 1999;Logsdon et al, 2006). With transmission electron microscopy (TEM), Johnstone et al (2008Johnstone et al ( , 2011 showed the structure of a crayfish nerve terminal with single vesicle resolution and an approach to estimate a range, with incorporating stereological errors, in measuring the location of vesicles in regard to the presynaptic membrane. Rarely are errors in location or distance dealt with from measurements utilizing TEM; however, such considerations are valuable Feuerverger et al, 2000;Kim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since serotonin increases the number of vesicles that are released with evoked stimulation, and since it promotes recovery during depression, it is apparent that there is some modulation of the vesicle pools for enhancing the probability of fusion with serotonin present (Johnstone et al, 2008;Logsdon et al, 2006;Sparks et al, 2004). Models that would explain the dynamics of the vesicle pools within the presynaptic nerve terminal during low frequency stimulation, as opposed to a depressed state, also need to be considered among the various experimental protocols that are possible with this preparation.…”
Section: Discussionmentioning
confidence: 99%
“…To observe the excitatory postsynaptic potentials (EPSPs) of the tonic or phasic neurons, one of the isolated axons in the nerve bundle is stimulated by a suction electrode ( Figure 11) connected to a Grass stimulator while intracellular potentials in the muscle are monitored (Johnstone et al, 2008). Stimulation at 70 Hz is applied to the tonic axon in order to promote a facilitated response for the low output NMJs, or a single pulse (1 Hz) is applied to the phasic axon in order to obtain large EPSPs of the high output NMJs as shown in Figure 12.…”
Section: ) Physiological Profilesmentioning
confidence: 99%
See 1 more Smart Citation